The Economic Impact of Deepening Trade Agreements - Lionel Gérard Fontagné; Nadia Rocha; Michele Ruta; Gianluca Santoni (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper explores the economic impacts of preferential trade agreements, conditional on their level of ambition. We cluster 278 agreements, encompassing 910 provisions over 18 policy areas and estimate the trade elasticity for the different clusters. We then use these elasticities in a series of general equilibrium counterfactual situations for endowment economies, revealing that deepening existing agreements (the intensive margin of regional integration) could boost world trade by 5 percent and world GDP by 1 percent. The expected gains from deepening agreements within or across regions vary depending on the initial depth of agreements and the size of regional markets.
Keywords: F14; F15; 330; preferential trade agreements; deep integration; structural gravity; general equilibrium